Corporate loans, banks' internal risk estimates and central bank collateral: Evidence from the euro area - Alessandro Calza; Julius-Benjamin Hey; Alessandro Parrini; Stephan Sauer (European Central Bank (ECB), 2021)
We use a unique dataset of ratings for euro area corporate loans from commercial banks' internal rating-based (IRBs) systems and central banks' in-house credit assessment systems (ICASs) to investigate whether banks' IRB ratings underestimate the credit risk of their corporate loan portfolios when the latter are used as collateral in the Eurosystem's monetary policy operations. We are able to identify systematic risk underestimation by comparing the IRB ratings with those produced for the same borrowers by the ICASs. Our results show that while they are on average more conservative than ICASs for the entire population of rated corporate loans, IRBs are significantly less conservative than ICASs for those loans that are actually used as Eurosystem collateral, particularly for large loans. The less conservative estimates of risk by IRBs relative to ICASs can be partly explained by banks' liquidity constraints, but not by their degree of capitalisation. Overall, our findings suggest the existence of a collateral-related channel through which the use of IRB ratings may influence the internal estimation of risk by banks.
Keywords: G21; G28; 330; Internal ratings; probability of default; banking regulation; central bank liquidity